Millennium declaration, rights and constitutions - Ghai, Yash 1938-; Cottrell, Jill; United Nations Millennium Campaign; United Nations Development Programme. Regional Centre in Bangkok (New York Oxford University Press, 2011)
Study on MDGs and human rights aims which should be part of constitutional reforms moderated by United Nations Millennium Campaign and United Nations Development Programme. Regional Centre in Bangkok.
"UNDP."
Includes bibliographical references and index.